?SYNTHESIS, AN'FIMICROBIAL AND ANTIAFLATOXIGENIC ACTIVITIES OF SOME BENZOFURAN CONTAINING 1,2,4-TRIAZOLE, 1,3,4-THIADIAZOLE AND OXADIAZOLE DERIVATIVES (Biological Sciences - PJSIR, 1995)
Alkaline hydrolysis of 9-methoxypsoralene-4-sulfonamide derivatives (Ia-d) using potassium hydroxide and dimethyl sulfate, afforded 3-propenoic acid derivative (IIa-d) which inturn were converted to 3-propenoic acid chlo- ride (IlIa-d) by the action of thionyl chloride in boiling toluene. Condensation of the latter compounds with thiosemicarbazide gave the corresponding carbonyl thiosemicarbazide derivatives (IVa-d). Cyclization of the latter compounds using boiling 5% sodium hydroxide solution gave 5-mercapto-I,2,4-triazolyl-3 derivatives (Va-d), using O-phosphoric acid gave 5-amino-I,3, 4-thiadiazolyl-3-derivatives (VIa-d) and using DCC gave 5-amino-l, 3, 4- oxadiazolyl-2-derivatives (VIla-d), respectively. Also,theantimicrobialand antiaflatoxigenicactivities ofcompounds (Va-d), (VIa-d) and (VIla-d) were investigated.